Основные морфологические особенности головного мозга и черепномозговых нервов дельфинов и других китообразных. Сообщение II - Агарков, Г.Б.; Слезин, В.Б.; Хоменко, Б.Г. (Вестник зоологии, 1975)
Data from literature and the authors own ones were analyzed concerning morpholo gy of the central and certain areas of the peripheral nervous system in dolphins and other Cetacea. The peculiarities are shown in organization of spinal cord, brain stem, subcortex, cerebral cortex, cerebellum and several craniocerebral and spinal nerves, hypaxial and epaxial nerve stems.